Jonathan Edwards’ Exegesis of Genesis 6:1-4 - WANG, Donald (中国基督教研究（ISSN：3068-479X）, 2025)
Jonathan Edwards is one of the great American Theologians in American church history. Jonathan Edwards understands the identity of the “sons of God” as the children of the church and this interpretation applies to his exegesis of Gen 6:3. His focus is not on רוחי in Gen. 6:3, but on “my Spirit shall not always strive with men”, and this phrase shows God’s patience and judgment, this understanding does shed light in the study of this passage.